Variasi Bahasa Tukul Arwana di Acara Bukan Empat Mata Trans 7 Dikaji dari Teori Etnografi Komunikasi Dell Hymes - Sigit Marteja (ESTETIK : Jurnal Bahasa Indonesia, 2019)
Analyzed from Dells Hymmes's ethnographic communication theory. This research uses descriptive qualitative methodology. Consists of eight speech acts: a. arrangement b. participant c. ends d. act e. key f. instrument g. norm h. Genre. Basically, all research data are taken from the program "Not Four Eyes" in Jakarta Trans 7. The data comes from Tukul Arwana's speech acts. Data analysis was performed in series as follows: Codification, data editor, data presentation and inference. The results showed that the variation of Tukul Arwana language has special characteristics (Indiocretic), which means it has directive, expressive, contextual, contact, Meta linguistic, and poetic functions. The use of slanted material for students is the ability of class XI students to respond to television programs.